PENGEMBANGAN LIFE SKILL SISWA MADRASAH MELALUI KEGIATAN EKSTRAKURIKULER BERKEBUN - Efferi, Adri (EDUKASIA, 2017)
DEVELOPING OF MADRASAH STUDENTS’ LIFE SKILL THROUGH GARDENING EXTRACURRICULAR ACTIVITY. The reason doing this study is to answer hard critics from the society as stakeholders for Education. It is about the exist of the Madrasah, Islamic School. It is viewed as an organization which haven’t give a good solution for both trouble in society; piss-poor and jobless. We use qualitative approach, interview, and collecting data technique to get data for this study. The results are: first, to reject arguments that the Madrasah graduation is only clever on religion, Madrasah Abadiyah Kuryokalangan Gabus Pati do gardening extracurricular to develop students’ life skill. This step makes the students develop their human talent in a maximum way and they have something to stand on the society. Second, there are a balance between life skill development through gardening activities with core curriculum that learnt in the class. As the Qur’an Hadist philosophy; the gardening techniqueare the practices from science teory and the gardening managing are the practises from Sociology teories.